Characteristics of the intelligent decision support system for precision medicine (IDSS4PM) - Mosavi, Nasimsadat (2022)
Reducing medical errors, increasing the performance of treatments, cutting the cost of overtreatment, meeting the patient’s expectations, and finally save more lives, are some of the major benefits of Intelligent Decision Support System for Precision Medicine(IDSS4PM). This paradigm intends to explore them in the healthcare domain. This study aims to introduce the architecture and remarkable features of such a framework where Simon’s model of decision-making supports the rationality of the proposed paradigm.